Homeopathic Management of Gastroesophageal Reflux Disease (GERD): Evidence Based Case Report - Nadgauda, Sameer S.; Raut, Ragini M.; Shaikh, Nilofer M. (Journal of Neonatal Surgery, 2025)
Background: Gastroesophageal Reflux Disease (GERD) is a chronic condition where stomach acid frequently flows back into the esophagus, the tube connecting the mouth and stomach. This backwash, known as acid reflux, can irritate the lining of the esophagus. GERD occurs when the lower esophageal sphincter, a muscle that acts as a valve between the esophagus and stomach, weakens or relaxes abnormally, allowing stomach contents to rise. Common symptoms include heartburn, regurgitation of food or sour liquid, and difficulty swallowing. GERD can also lead to complications like esophagitis, Barrett's esophagus, or even esophageal cancer if left untreated. Lifestyle factors such as obesity, smoking, and certain dietary habits can increase the risk of GERD. Management typically involves lifestyle changes, medications to reduce stomach acid, and in severe cases, surgical interventions. Understanding GERD's causes and symptoms is crucial for effective treatment and improving quality of life. Methods: Homeopathic medicine selected based on state of mind, in low potency, single medicine and infrequent repetition, can be implemented with good results. Sulphur in 30 potency stimulation can be implemented on symptom similarity. Result: In GERD with regurgitation and vomiting ,unable to sleep after 3 doses of homeopathic medicine Sulphur in 30 potency at every 15 mins time interval regurgitation reduced and patient was comfortable, with subsequent follow up. Patient recovered within 3 wks with no further relapse. Conclusion: Accuracy in homeopathic prescription by concept of individuals' mental state during the illness can yield good clinical results in case of Diagnosed case of GERD, after treatment with homeopathic medicine, clinical and evidence based results can be achieved.